Zwei mit Cyphon kotanus YOSHITOMI, 2009 verwandte neue Arten aus Borneo (Coleoptera, Scirtidae) (182. Beitrag zur Kenntnis der Scirtidae). - Klausnitzer, Bernhard (Contributions to Entomology = Beiträge zur Entomologie, 2013)
Two new species of the genus Cyphon Paykull, 1799 are described from Borneo and are compared with C. kotanus Yoshitomi, 2009, also occurring on Borneo. Based on the configuration of the 9th sternite and the penis, the erection of a group of its own for the three species appears justified (Cyphon kotanus-Subgroup). An identification key is provided.Nomenclatural Actslabratus Klausnitzer, 2013 (Cyphon), spec. nov.sinuatosternalis Klausnitzer, 2013 (Cyphon), spec. nov.